Global and regional echocardiographic strain to assess the early phase of hypertrophic cardiomyopathy due to sarcomeric mutations. (5th May 2019) - Baudry, Guillaume; Mansencal, Nicolas; Reynaud, Amelie; Richard, Pascale; Dubourg, Olivier; Komajda, Michel; Isnard, Richard; Réant, Patricia; Charron, Philippe
Abstract: Aims: Hypertrophic cardiomyopathy (HCM) is a genetic disease with delayed cardiac expression. Our objective was to characterize left ventricular (LV) myocardial strain by two-dimensional echocardiography in sarcomeric mutation carriers before the hypertrophic stage. Methods and results: We studied 140 adults [derivation cohort ( n  = 79), validation cohort ( n  = 61)]. The derivation cohort comprised 38 confirmed HCM patients with hypertrophy (LVH+/Gen+), 20 mutation carriers without LV hypertrophy (LVH−/Gen+), and 21 healthy controls. LV global longitudinal strain was not different in LVH−/Gen+ compared with controls [20.6%, interquartile (IQ): 18.3/24.2 vs. 22.9%, IQ: 20.9/26.8] but was reduced in LVH+/Gen+ patients (14.1%, IQ: 11.8/18.5, P  < 0.001). Regional peak longitudinal strain was significantly decreased in LVH−/Gen+ when compared with controls in four segments: basal anteroseptal (BAS) wall ( P  = 0.018), basal inferoseptal wall ( P  = 0.047), basal inferior wall ( P  = 0.006), and mid anteroseptal wall ( P  = 0.022). Receiver operating characteristic analysis identified that BAS strain <16.5% had a sensitivity (Se), specificity (Sp), positive and negative predictive values (PPV, NPV) of 57%, 90%, 82%, and 67%, respectively, to differentiate LVH−/G+ patients from controls. Similarly, the accuracy of a ratio between basal inferoseptal/basal anterolateral (BIS/BAL) strain <0.76 was 73%, 92%, 82%, and 64%, respectively (Se/Sp/PPV/NPV). In the validation cohort, the accuracy of BAS and BIS/BAL was 39%/93%/87%/57% and 55%/96%/95%/64% (Se/Sp/PPV/NPV), respectively, to differentiate the LVH−/Gen+ group from controls. Conclusion: Regional longitudinal strain, but not global strain, was significantly reduced at the early stage of HCM before LV hypertrophy. This suggests that the inclusion of strain (BAS < 16.5%; BIS/BAL < 0.76) in the evaluation of HCM relatives would help identify mutation carriers and early LV abnormalities.